The management of care in setting up an area of health care in the community school - Balbino, Carlos Marcelo; Silvino, Zenith Rosa (Online Brazilian Journal of Nursing, 2009)
Exploratory nature of this research aims to recognize the causes of problems related to health community school, served in the Division of Educational Guidance and prepare schedule of Health Education to work within an appropriate place: Area of health care in Institute of Culture Technology - ICT in the city of Volta Redonda - RJ. The interest in developing this research was due to a large number of clinical events in the school environment. The approach is quantitative and processing of data through the EpiInfo 3.3.2. The method of data collection will be through a form that all the focus of care performed by nurses to the school community, ie students, staff and relatives attending the ICT. It is intended to establish an area of health care to the clients is preserved in its intimacy, avoiding excessive exposure and embarrassment.